Biological sulfur cycling in Finland’s deep groundwater - Bomberg, Malin; Nuppunen-Puputti, Maija; Purkamo, Lotta; Nyyssönen, Mari; Miettinen, Hanna; Kietäväinen, Riikka (University of Helsinki, 2024)
The sulfur cycle is key for microbial life in the deep subsurface, where sulfate is one of the few electron acceptors available. Sulfate reducing bacteria (SRB) are commonly found in Finnish deep groundwater, but the complete biological cycling of sulfur compounds is still not well known. Despite the assumed lack of oxygen in deep groundwaters, studies hint at oxygen production that might support oxygen-requiring microbial processes, such as sulfide oxidation, although this hasn't been studied in detail yet. This study examined groundwater samples from six sites in the Finnish part of the Fennoscandian Shield, covering depths from 100 to 2400 meters. The research used uniform molecular analysis techniques, including qPCR for bacterial and SRB abundance and metagenomics for microbial metabolisms. Results show varied bacterial and SRB abundance across sites, with the highest numbers in Kopparnäs and Liminka and the lowest in Pyhäsalmi. Community composition varied, with distinct clusters identified. Metagenomic analyses revealed pathways for sulfate reduction and thiosulfate and sulfide oxidation in several sites, indicating active sulfur cycling, including both anoxic and oxygen-demanding processes.